(untitled) (Texas Journal of Multidisciplinary Studies, 2022)
In this article, the architecture of Uzbekistan is influenced by various architectural traditions, such as Islamic architecture, Persian architecture, and Russian architecture. Temurid architecture is the pinnacle of Uzbekistan’s Islamic art. The magnificent buildings erected by Timur and his successors in Samarkand and Herat contributed to the spread of the influence of the Ilkhanid school of art in India, leading to the emergence of the famous Mongolian school of architecture. It is said that the architecture of the Temurids began with the sanctuary of Ahmad Yas-savi in modern Kazakhstan and ended with the mausoleum of Temur Gur-i Amir in Samarkand